Предмет: Алгебра,
автор: Bullet111
Упростить выражение cos⁴x-sin⁴x-cos²x+sin²x
Ответы
Автор ответа:
0
(cos⁴x- sin⁴x)..можно расписать как (cos²x - sin²x ) (cos²x+sin²x)..
(cos²x-sin²x)(cos²x+sin²x)-(cos²x-sin²x)=(cos²x-sin²x)(cos²x+sin²x-1)...есть формула cos²x+sin²x=1...(cos²x-sin²x)(1-1)=(cos²x-sin²x)..можно ещё расписать...cos²x =1-sin²x....(1-sin²x-sin²x)=(1-2sin²x)=cos2x
Ответ: cos2x
(cos²x-sin²x)(cos²x+sin²x)-(cos²x-sin²x)=(cos²x-sin²x)(cos²x+sin²x-1)...есть формула cos²x+sin²x=1...(cos²x-sin²x)(1-1)=(cos²x-sin²x)..можно ещё расписать...cos²x =1-sin²x....(1-sin²x-sin²x)=(1-2sin²x)=cos2x
Ответ: cos2x
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Английский язык,
автор: sladkaya15kartoshka
Предмет: Физика,
автор: aidanabaktyiarova
Предмет: Математика,
автор: rtybnm71
Предмет: Математика,
автор: Dokuchaeva202